Approximation Theorems for Generalized Complex Kantorovich-Type Operators - N. I. Mahmudov; M. Kara (Journal of Applied Mathematics)
The order of simultaneous approximation and Voronovskaja-type results with quantitative estimate for complex q-Kantorovich polynomials () attached to analytic functions on compact disks are obtained. In particular, it is proved that for functions analytic in , , the rate of approximation by the q-Kantorovich operators () is of order versus for the classical Kantorovich operators.